Study of wireless LAN security issues - Mar, Kai Liat. (2008)
It is well known that 802.11 encryption system using Ron's Code 4 (RC4) is weak and easily breakable. The aim of this project is to study the weaknesses of the system through literature search and proposed a possible solution to enhance the encryption system of 802.11 standard.